ANALISIS KANVAS MODEL BISNIS PEMBENIHAN IKAN PATIN DI PASIR GAOK, KABUPATEN BOGOR - Apriana Vinasyiam; Belinda Astari; Yanti Inneke Nababan; Jose Manuel Arrealdo Sinaga; Mochamad Syaiful Fiqri Ramadhan; Erlyando Yohanes; Azizah Zahra; Aulia Puan Azzahra; Ananda Sholekha Maulidiya (Universitas Mataram, 2026)
Aquaculture is a rapidly growing food production sector that plays a vital role in national food security. This study aims to analyze the business model of a Pangasius nursery farm located in Pasir Gaok, Rancabungur District, Bogor Regency, using the Business Model Canvas (BMC) framework. A qualitative descriptive approach was employed, with primary data collected through semi-structured interviews, field observations, and documentation. The results indicate that the Pangasius nursery farm serves local collectors, market traders, and individual buyers, offering consistent fish quality and stable pricing. Feed constitutes the largest cost component, while revenue is mainly derived from the sale of fingerlings. The discussion highlights that business success depends on cost efficiency, effective technical management, and partnerships with research institutions that foster innovation and sustainability in aquaculture enterprises.